Divorce and Remarriage of Orthodox Copts in Egypt: The 2008 State Council Ruling and the Amendment of the 1938 Personal Status Regulations - Bernard-Maugiron, Nathalie (Islamic Law and Society, 2011)
In June 2008, the 1938 Personal Status Regulations for the Coptic Orthodox Church in Egypt were amended to limit the grounds for divorce to adultery and change of religion. This revision followed a ruling of the State Council requiring Pope Shenouda III, the head of the Coptic Orthodox Church, to grant a divorced Orthodox Copt a license to remarry. The amendments ended a long-standing conflict between the Egyptian national courts and the Coptic Orthodox Church regarding the effects of judicial divorce: prior to the revision, thousands of couples divorced before the courts were considered by the Church to be still married. However, by restricting the possibilities for Orthodox Copts to obtain a divorce, the 2008 amendments may lead to an increase in conversions to other religious faiths to escape application of the revised 1938 regulations. In this essay, I analyze the 2008 amendments, the State Council ruling, landmark decisions of the Court of Cassation, comments by legal scholars and articles in newspapers, in an effort to assess the current status of divorce and remarriage among Orthodox Copts in Egypt and the problems generated by the application of conflicts rules between non-Muslim personal status laws in case of inter-religious marriages. At the end of the essay, I mention developments that took place in June 2010 after the release of a new ruling by the State Council.